Amantadine in treatment of chronic hepatitis C virus infection? - Lim, J. K. (J Viral Hepat, 2005)
Summary.  Treatment of chronic hepatitis C (CHC) continues to be an important and growing challenge. As the response rate to FDA‐approved treatment improved over the past decade, we are facing increasing number of difficult‐to‐treat patients such as those who have failed prior anti‐viral therapy. The role of amantadine in the treatment of CHC remains unclear. Studies thus far have produced conflicting results, and type II error could not be excluded. This review summarized results published in the literature from 1997 to 2003, and reviewed the existing questions and controversies regarding the use of amantadine. Current literature suggests that amantadine is ineffective as monotherapy. Amantadine increased the sustained virologic response of certain treatment naïve patients when used in combination with interferon, and may be effective as an adjunct to interferon‐based combination therapy in some patients who have failed or relapsed on prior therapy. Factors such as small sample size, patient characteristics, and differences in treatment protocols including amantadine preparation and duration of therapy might explain the conflicting observations of various studies. Further investigations are needed to define optimal dosing and formulation of amantadine, and its appropriate role in management of CHC infection.